A NUMERICAL STUDY ON HAMMERSLEY SEQUENCE AND FIBONACCI BASED LATTICE RULE FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS: A NUMERICAL STUDY ON HAMMERSLEY SEQUENCE AND FIBONACCI BASED LATTICE RULE FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS - Todorov, Venelin; Dimov, Ivan; Dzurov, Valerij; Stanchev, Tosho; Tsvetkov, Ilian; Dimitrov, Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper we make a numerical study between Hammersley quasi-random sequence and Fibonacci based lattice rule for computing multidimensional integrals. The two methods have not been compared before and both are recommended in case of smooth integrands. The two quasi-Monte Carlo approaches are completely different thus it is a question of interest which one of them outperforms the other. We consider a case study with smooth integrand functions of different dimensions. A comparison with Sobol sequence for a fixed computational time is given.